Pengaruh Penerapan LKPD Berorientasi Model Pembelajaran Generatif Terhadap Pencapaian Kompetensi Fisika Siswa Kelas XI SMAN 12 Padang - Resti Sundari; Hidayati Hidayati; Letmi Dwiridal (Universitas Negeri Padang, 2018)
Student's interest and motivation toward physics is still low. One of the reasons is that the teaching materials used are not yet varied and the lesson model used by the teacher is less able to invite the students to find and solve the physics problem, so that the students are less interested and active in the learning that causes the low of the students. To overcome this, conducted research that aims to determine the effect of LKPD application of generative learning model on the ability of students of class XI SMAN 12 Padang. The population in pre-experimental studies with a one-shot case study design was the students of grade XI in SMAN 12 Padang enrolled in the 2017/2018 school year. In this research, experiments conducted without controlling for the variables being moderate and not preferred are. Samples in this research using purposive sampling technique. Assessment instruments used in the measurement of observation, knowledge competence in the worksheet. The data generated in this study were analyzed using regression test for knowledge and usage competence. Based on data analysis that has been done, obtained data for. In the attitude competence of students to increase every week. In the knowledge competence increases after being given treatment with percentage of influence> 18%. While the competence of teachers percentage of influence> 13%. Can be concluded that there is influence of LKPD application of generative learning model to student of class XI SMAN 12 Padang.